2017
DOI: 10.1098/rsos.170808
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and pathogen transmission in pastoral cattle contact networks

Abstract: Capturing heterogeneity in contact patterns in animal populations is essential for understanding the spread of infectious diseases. In contrast to other regions of the world in which livestock movement networks are integral to pathogen prevention and control policies, contact networks are understudied in pastoral regions of Africa due to the challenge of measuring contact among mobile herds of cattle whose movements are driven by access to resources. Furthermore, the extent to which seasonal changes in the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 51 publications
2
68
2
Order By: Relevance
“…The homogeneous mixing assumption used at the within-ward level has previously been shown to be useful for developing strategic understanding, even in highly spatially driven scenarios [161], but more detailed recommendations would require modelling of within-ward heterogeneity supported by higher resolution data. This assumption may be less realistic for small urban wards where cattle are tethered, though in larger pastoral and agro-pastoral wards, shared natural resource points might make homogeneous mixing more appropriate (GL Chaters 2017, unpublished data, and [158]). Similarly, while the assumption that cattle-to-market movements occur from adjacent wards is consistent with two authors' expert knowledge of livestock management practice (O.M.N.…”
Section: Discussionmentioning
confidence: 99%
“…The homogeneous mixing assumption used at the within-ward level has previously been shown to be useful for developing strategic understanding, even in highly spatially driven scenarios [161], but more detailed recommendations would require modelling of within-ward heterogeneity supported by higher resolution data. This assumption may be less realistic for small urban wards where cattle are tethered, though in larger pastoral and agro-pastoral wards, shared natural resource points might make homogeneous mixing more appropriate (GL Chaters 2017, unpublished data, and [158]). Similarly, while the assumption that cattle-to-market movements occur from adjacent wards is consistent with two authors' expert knowledge of livestock management practice (O.M.N.…”
Section: Discussionmentioning
confidence: 99%
“…The conservancy has ~8,500 cattle, which are grazed during the day and stockaded in corrals during the night. The corrals are moved often based on management's appraisal of pasture availability and ecological preservation of the grazing areas (VanderWaal et al, 2017). OPC has ~1,200 buffalo in herds of between 30-200 individuals.…”
Section: Description Of the Study Sitementioning
confidence: 99%
“…However, during the rainy season there were farms which failed to achieve the minimum scores to be placed in this category. The transmission of pathogens can be influenced by different factors, such as population density and resources distribution, among others [ 17 ]. Due to the availability and distribution of pastures during the dry season, it was observed that animals would spread looking for good sources of grass, making their interactions scarce.…”
Section: Discussionmentioning
confidence: 99%